Teacher Advisor Program in Guidance and Counseling: A Literature Review - Rifqoh, Fany (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2024)
The current era of industrial revolution demands critical, creative, communicative and collaborative thinking processes. These processes can be carried out through the learning process. Of the several demands of the 21st century, the thing that is most fundamental and requires cooperation between one individual and another is collaborative. Collaboration between teachers and students can be created through activities combined into the teacher advisor program. In line with this. This article will discuss the teacher advisor program as a basis for developing collaborative skills in schools. The method used is descriptive. The data sources in this research were obtained through literature reviews originating from expert opinions as well as several relevant articles related to the topic. Several results such as definitions, objectives, benefits regarding the teacher advisor program will later be discussed and concluded.